Emigration of Icelandic elite skiers: In search for opportunities to achieve their goals - Kristjánsson, K. P. V. (Mittuniversitetet (Mid Sweden University), 2020)
The migration of athletes is a known phenomenon but the reasons behind it are based on the athletes` motivation as well as their kind of sport. Athletes migrate for a variety of reasons, including their own motivation and the nature of their sport. The aim of this study was to understand why Icelandic elite ski racers emigrate to achieve their goals and how they adapt to new surroundings while training and racing. To understand in greater detail their reasons for emigrating, as well as how their adapt to their surroundings, 8 members of the Icelandic national team in alpine and cross-country skiing for the 2018-2019 or 2019-2020 seasons who had migrated participated in semi-structured interviews.The factors that played a role in their migration included a desire for better training conditions as well as more challenging competition both in training and racing. Overall, they adapted well to the changes involved and bonded both with teammates and individuals outside of the sport.